2010
DOI: 10.1002/jssc.200900663
|View full text |Cite
|
Sign up to set email alerts
|

Determination of aflatoxins B1, B2, G1, G2 and ochratoxin A in animal feed by ultra high‐performance liquid chromatography–tandem mass spectrometry

Abstract: A rapid and simple method was developed to determine aflatoxins B1, B2, G1, G2 and ochratoxin A in animal feed and pet foods by UHPLC-MS/MS. Because the complexity of the evaluated matrices, the proposed method is based on sonication extraction using an ACN/water mixture (80:20 v/v) followed by a clean-up step utilising C(18) as sorbent. Performance parameters of the method were evaluated, including linearity, trueness, precision and LOQ. Good linearity was found for all mycotoxins, with determination coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 33 publications
4
8
1
Order By: Relevance
“…Results in this study, however, reveal a clear indication of an uncommon AF occurrence pattern with higher amounts of the less potent AFB 2 and AFG 2 dihydro-derivatives and lower incidences of AFB 1 and AFG 1. Similar findings with high AFG 2 content and trace amounts of other aflatoxins have been reported in nut and dried fruit samples [ 13 ], animal feeds [ 14 ], cereal samples [ 15 ], raw maize and groundnut samples [ 16 ], and palm kernel cake [ 17 ]. Mngadi et al [ 3 ], also mentioned similar ratios in preliminary work done on South African animal feeds.…”
Section: Discussionsupporting
confidence: 82%
“…Results in this study, however, reveal a clear indication of an uncommon AF occurrence pattern with higher amounts of the less potent AFB 2 and AFG 2 dihydro-derivatives and lower incidences of AFB 1 and AFG 1. Similar findings with high AFG 2 content and trace amounts of other aflatoxins have been reported in nut and dried fruit samples [ 13 ], animal feeds [ 14 ], cereal samples [ 15 ], raw maize and groundnut samples [ 16 ], and palm kernel cake [ 17 ]. Mngadi et al [ 3 ], also mentioned similar ratios in preliminary work done on South African animal feeds.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, other studies recently conducted in several European countries showed only a modest presence of aflatoxinsin dog foods, often in non-quantifiable traces or, in any case, in very small concentrations (Martins et al, 2003;López Grío et al, 2010;Böhm et al, 2010). This situation, confirmed by the results of the present study, is likely to be attributable to the effectiveness of the control system currently in force in Europe, particularly with respect to aflatoxins in feed intended for animals.…”
Section: Discussioncontrasting
confidence: 79%
“…Razzazi et al (2001), for example, quantified this mycotoxin in 60% of pet food samples (a total of 10 dry and 30 wet foods, respectively) purchased in the Polish and Austrian markets, with analogous percentages of positivity in the two types of products (respectively 40% and 43%), albeit with different levels of contamination (in the range of 0.21-13.1 g/kg and 0.22-0.8 g/kg, in dry and wet pet foods, respectively). Other studies conducted in Europe have shown, in contrast, a more sporadic OTA contamination in the pet food samples examined, for the most part in rather modest concentrations, always lower than 5 g/kg (Martins et al, 2003;López Grío et al, 2010;Böhm et al, 2010). In a study conducted on 40 dry and wet dog foods available in the Austrian and German markets, Songsermsakul et al (2007) observed a range of OTA contamination (from 7 to 40 g/kg) similar to the one found in the present study, though this mycotoxin was quantifiable in only 12.5% of the foods.…”
Section: Discussionmentioning
confidence: 91%
“…UPLC/UHPLC coupled to triple quadrupole mass spectrometer, in selected reaction monitoring (SRM) mode, is nowadays considered as one of the most selective and sensitive techniques for quantification and confirmation of organic contaminants and residues in food/feed. Some applications of this technique on mycotoxin analysis field have been recently reported [73][74][75][76][77][78][79][80].…”
Section: Determination Of Mycotoxins By Liquid Chromatography Tandem mentioning
confidence: 99%